Multi material 3D printing of PLA-PA6/TiO2 polymeric matrix: Flexural, wear and morphological properties. (November 2022) - Kumar, Sudhir; Singh, Rupinder; Singh, Mohit; Singh, TP; Batish, Ajay
The poly-lactic acid (PLA), bio compatible polyamide (PA6) and TiO2 has established bio-medical applications especially in 3D printing of scaffolds. But hitherto little has been reported on improving the performance of multi-material matrix for PLA-PA6/TiO2 especially in 3D printing application of biomedical scaffolds. The anti-bacterial properties of PA6/TiO2 make it worthy to be explored with PLA matrix in multi layered fashion on the platform of fused deposition modeling (FDM) being low cost 3D printing technology for in house development of scaffolds. In this work an effort has been made for in-house development of feedstock filaments of PLA and PA6/TiO2 based polymeric composite matrix on twin screw extrusion (TSE) machine. Further the feedstock filament wires were used on FDM to establish the flexural, wear and morphological properties of multi-material 3D printed functional prototype. The results of the study suggest that for flexural strength, infill speed: 90mm/s; infill pattern: triangular and layer combination as 5 consecutive layers of PLA and 5 consecutive layers of PA6/TiO2 are the optimized conditions for FDM printing. The wear testing results suggest that the composite of PA6/TiO2 held low wear rate (823 µm) in comparison to PLA (wear rate: 1092 µm). Further porosity testing (based upon optical photomicrographs) at ×100 and fractured surface analysis at ×30 supported the observed trends for flexural and wear testing. The photomicrographs of fractured surface were 3D rendered to predict the role of surface roughness (Ra) profile for flexural properties. The mechanical and morphological observations are also supported with scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) analysis.